Conformational dynamics of carbohydrates: Raman optical activity of d-glucuronic acid and N-acetyl-d-glucosamine using a combined molecular dynamics and quantum chemical approach1. Issue 8 (28th February 2015) - Mutter, Shaun T.; Zielinski, François; Cheeseman, James R.; Johannessen, Christian; Popelier, Paul L. A.; Blanch, Ewan W.
<x xml:space="preserve">Abstract</x> Raman optical activity combined with state-of-the-art computational approaches successfully probes the conformational space of two important carbohydrates.